Pengaruh Pengaturan Komposisi Media Tanam Organik Terhadap Pertumbuhan Dan Hasil Tanaman Ubi Jalar ( Ipomoea batatas L.) Dengan Sistem Tabilampot - Mohamad Ghufron Mardiyanto; Siti Muslikah; N Nurhidayati (Universitas Islam Malang, 2020)
Sweet potatoes are an alternative source of carbohydrates that have high nutritional content. Development of sweet potato cultivation methods needs to be done to overcome the decrease of productive agricultural land due to land conversion. This study aimed to test the effect of differences in the composition of the growing media on the growth, yield, and quality of sweet potato. This study was a pot experiment using a Randomized Block Design (RBD) with 7 treatments and 5 replications. The types of treatments tested were P0: 100% soil + inorganic fertilizer; P1: 50% soil + 50% cow manure; P2: soil 50% + vermicompost 50%; P3: soil 50% + biochar rice husk 25%, cow manure 25%, P4: soil 50% + biochar rice husk 25% + vermicompost 25%, P5: soil 50% + cocopeat 25% + cow manure 25%, P6: soil 50% + cocopeat 25% + vermicompost 25%. The research results showed that the composition of the growing medium significantly affected plant growth and yield. The results of the statistical analysis showed that the treatments of P4 and P6 gave the highest growth, while the high yield of fresh weight of tubers per pot were found in the treatments P1, P2, P3, and P4 by 165.59 g, 143.38 g, 171.56 g, and 144.80 g, respectively. The highest number of tubers was found in treatment P6 by 7.66 tubers. The highest yield of dry matter was also found in treatments P1, P2, P3, and P4 by 59.91 g, 51.73 g, 59.02 g, and 48.59 g, respectively. Based on the research results, it can be recommended that the cultivation of sweet potato plants in pots can be carried out using porous growing media in a container that is sufficient and available balanced nutrients for the development of plant tubers.Keywords: Vermicompost, composition of growing media, Sweet Potatoes, Yield, Quality